Knowledge, attitude and practices towards human papillomavirus infection, vaccination and cervical cancer among paramedical students at a Sri Lankan University - H. S. Priyadarshani; S. Arunasalam; F. Noordeen (Sri Lankan Journal of Infectious Diseases, 2023)
Introduction: Human papillomavirus (HPV) infection is one of the most common sexually transmitted infections, and HPV is an aetiological agent for cervical cancer (CC). In Sri Lanka, CC is the second most frequent cancer affecting women. The present study was undertaken to determine knowledge, attitude and practices (KAP) regarding HPV infection, vaccination and CC among paramedical students of the Faculty of Allied Health Sciences (FAHS), University of Peradeniya.